Debating as a Systematic Teaching Technique to Promote HOTS (Higher Order Thinking Skill) - Dipta, Dinar; Haikal, Muhammad; Nuraini, Eka Indah; Virgiyanti, Diska Fatima; Fachriza, Aries; Mahastu, Puput Jianggi; Ramadhani, Annisa (Universitas PGRI Madiun, 2023)
Enhancing speaking skills is essential, especially for EFL learners who find it challenging to perform English well since it is not their native language. In this case, a debate is promoting a new perspective among the EFL learners that this technique gives them opportunities to have discussions; they can use the language freely; without any forces and strict rules that make them be motivated to speak actively. The instructors can employ this technique to accommodate students with differing learning styles. Debating as a teaching technique brings many advantages to EFL learners, including promoting higher order thinking skill, mastering the course topics, increasing the speed of learning, enhancing social skills, promoting evaluation power, promoting mental health, and leading to creative learning. However, this technique carries its own opponents, is limited, and is challenging to apply. Therefore, this paper aims to introduce debate as an instructional technique, review earlier studies on it, compare it with other similar procedures, and discuss its limitations and challenges as well as its benefits, especially to EFL learners.